(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research seeks to discuss the topic of temporal structure techniques in the writer Lutfia Al-Dulaimi’s collection of stories "Sufi Music" by applying the Russian formalists’ approach, as well as Todorov and Genette’s oral divisions regarding time formats. The author plays with the traditional sequential time with the mechanisms of anticipation and flashback that emerged strongly in this collection of stories, indicating the writer’s intentionality and critical and cognitive awareness of how to employ these modernist narrative techniques, as well as their artistic and aesthetic purposes in modern narrative poetry.